2020
DOI: 10.1186/s12891-020-03317-y
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-532-5p is implicated in the regulation of osteoporosis by forkhead box O1 and osteoblast differentiation

Abstract: Background: MicroRNAs (miRNAs) are critical regulators in osteogenesis and cartilage formation. This study was designed to investigate whether miR-532-5p plays a role in the regulation of osteoporosis. Methods: Osteoporotic fractures (OP group, n = 10) or osteoarthritis without osteoporosis (control group, n = 10) were selected as subjects in this study. Quantitative analysis of gene expression was performed by RT-PCR. Western blot was used to determine the expression levels of protein forkhead O1 (FOXO1). Bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…Furthermore, with an extension of immobilization, osteoblast activity continued to decrease, as reflected by the reduction of OCN expression, suggesting that the balance between bone resorption of osteoclasts and bone formation of osteoblasts was broken in immobilization-induced KOA rabbits. A previous study has indicated that low expression of OCN is observed in KOA subchondral bone with severe bone loss, resulting in a reduction of bone formation [52], while increasing the content of OCN can effectively promote osteoblast activity in damaged bone [53]. Our study demonstrated that acupotomy and electroacupuncture effectively promoted bone formation by activating OCN expression.…”
supporting
confidence: 65%
“…Furthermore, with an extension of immobilization, osteoblast activity continued to decrease, as reflected by the reduction of OCN expression, suggesting that the balance between bone resorption of osteoclasts and bone formation of osteoblasts was broken in immobilization-induced KOA rabbits. A previous study has indicated that low expression of OCN is observed in KOA subchondral bone with severe bone loss, resulting in a reduction of bone formation [52], while increasing the content of OCN can effectively promote osteoblast activity in damaged bone [53]. Our study demonstrated that acupotomy and electroacupuncture effectively promoted bone formation by activating OCN expression.…”
supporting
confidence: 65%
“…Some data also links expression changes of selected miRNAs with insulin sensitivity. For instance, miR-532-5p was associated with IR in females via regression analysis [ 44 ] as well as confirmed to target FoxO1 [ 45 ]. Further, let-7 family is a well-known regulator of glucose homeostasis and IR [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…By reviewing the literature on phenotypes related to physical frailty, we identified a total of 57 miRNAs associated with physical phenotypes, resumed in Table S1 [ 67 , 68 , 69 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 ]. An inspection of their characteristics revealed that they belong to three main groups: muscle-related miRNAs, inflamm-miRNAs and mitochondrial miRNAs (mitomiRNA).…”
Section: Mirnas As Biomarkers Of the Physical Domain Of Frailtymentioning
confidence: 99%